Characteristics and mechanism of modified hydrotalcite for coal spontaneous combustion preventing. (15th February 2023) - Shu, Pan; Zhang, Yanni; Deng, Jun; Duan, Zhengxiao; Zhai, Fangyan
Abstract: Hydrotalcite is a new fire-fighting material with a sound effect of preventing the spontaneous combustion of coal. In this paper, hydrotalcite (Zn–Mg–Al-LDHs) and rare earth element Ce-modified hydrotalcite (Zn–Mg–Al–Ce-LDHs) inhibitor samples were prepared by the co-precipitation method, respectively. The surface morphology, dispersibility, and pyrolysis properties of the inhibitor were characterized by thermogravimetric experiments. Based on thermogravimetric experiments, the effects of hydrotalcite and modified hydrotalcite containing rare earth element Ce on the spontaneous combustion characteristics of coal were studied. Combined with thermodynamic parameters, the inhibition mechanism of coal spontaneous combustion was analyzed. The results showed that Zn–Mg–Al-LDHs and Zn–Mg–Al–Ce-LDHs inhibitors were successfully prepared. Adding the two to coal can inhibit both coal samples, and the inhibition effect of Zn–Mg–Al–Ce-LDHs is more significant. The Zn–Mg–Al–Ce-LDHs inhibitor can effectively reduce the weight loss rate of coal, delay the critical temperature, and maximum weight loss rate temperature of coal samples by 6 °C and 31.5 °C, respectively, and increase the residual heat by 2.3%. The calculation of apparent activation energy shows that the average activation energies of Zn–Mg–Al–Ce-LDHs for inhibiting coal samples in the stages of water evaporation and gas desorption and thermal decomposition and combustion are 30935.256 J/mol and 76962.582 J/mol, respectively; 464.878 J/mol and 31914.233 J/mol higher than raw coal, respectively. Highlights: Ce promotes the regularity of LDHs crystal structure. The inhibition effect of modified hydrotalcite is in the first and third stages of CSC. Modified hydrotalcite can increase activation energy to inhibit CSC.